Small number of bidders and limited for procurement process established for service and support battalion to fight no. 21 (2013)
This paper aims to establish what are the main factors that motivate the existence of a small number of bidders being always the same in the participation to public bidding processes for the procurement of goods and services according to the state budget that allocates funds national defense ministry to this military unit , to meet the requirements according to a plan established by it needs to fulfill the mission. The different processes of the entity contracting for the supply of goods and services by public call which invites interested parties to holding onto the basis set make proposals , among which will be selected and accept the most suitable . Generate processes that do not allow to comply with the times and movements established in the plan proposed by the entity needs . Therefore, a clear need to identify the shortcomings which does not allow to implement the flowchart established by the tactical unit and System Objectives Public Procurement , where State institutions should work toward achieving these goals , which are contemplated in Decree 1510 of 2013 , which is governed by the system of procurement and public procurement , which seeks to optimize lead and get a larger number of participants in the call established in order to make the process more efficient, effective and efficient . Also in procurement processes that are currently underway evidenced by many factors, the lack of participation of a greater number of bidders , which becomes an obstacle of goals and objectives of the unit budget . With forms to those laid down in Article 209 of the constitution , the Ministry of Defence and its implementing units should develop their administrative, contractual processes , under the principles of equality, morality , economics , fairness and advertising. According to Decree 1510 of 2013 , provides that state agencies must comply with a manual identifies the different functions that recruitment procedures, pointing out the different aspects of the process , its local control and steps to follow in order to carry out the invitation public . As part of this research we find the wedges of non-participation of the suppliers at the time of convening the recruitment process in its various forms, considering that the entity does not have a bank to disclose marketing providers and creating the need you always have the same suppliers.